2012
DOI: 10.4028/www.scientific.net/amm.225.233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rotor Tip Gap Variation at the Rear Stages of an Axial Flow Compressor

Abstract: In this paper, detailed analysis of the tip flow of an axial compressor rotor blade has been carried out using the commercial CFD package ANSYS CFX. The rotor blade was designed such that it is reminiscent of the rear stages of a multi-stage axial compressor. The effects of varying tip gaps are studied using CFD simulations for overall pressure rise and flow physics of the tip flow at the design point and near the peak pressure point. Rig tests of a low speed research compressor rotor with 3% tip clearance pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A lot of research results have found that the TLF is an extremely complex three-dimensional viscous flow, which is importantly related to the internal flow loss and stall of the compressor. [1][2][3][4][5] Therefore, in order to further improve the performance of the compressor, it is of great significance to carry out research on the effect of the BTC on the performance of the compressor.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research results have found that the TLF is an extremely complex three-dimensional viscous flow, which is importantly related to the internal flow loss and stall of the compressor. [1][2][3][4][5] Therefore, in order to further improve the performance of the compressor, it is of great significance to carry out research on the effect of the BTC on the performance of the compressor.…”
Section: Introductionmentioning
confidence: 99%